Research on the spatial characterization of a 3D UAV air-to-ground channel model - Zhi ZHANG; Tianbo XIONG; Jianqiao CHEN; Nan MA (Tongxin xuebao)
To cope with the problem that the distribution assumptions of arrival angle and departure angle in existing geometry-based stochastic modeling (GBSM) for the unmanned aerial vehicle (UAV) air-to-ground (A2G) channel are too ideal to describe the spatial statistical property of the UAV A2G propagation environment precisely,considering the three-dimensional (3D) cylindrical A2G channel model,the spatial geometric characteristics of scattering regions were investigated analytically as corresponding to the angles of arrival and departure in both elevation and azimuth planes,which derived the probability density function (PDF) for the distribution of each angle.The effects of various parameters of channel model on the PDF were studied and simulation results prove that the derived PDF can describe the spatial statistical properties of UAV A2G channels more accurately,and can support the modeling of A2G communication channels well.